2019
DOI: 10.1002/pc.25361
|View full text |Cite
|
Sign up to set email alerts
|

Flammability, thermal stability and mechanical properties of polyvinyl alcohol nanocomposites reinforced with delaminated Ti3C2Tx (MXene)

Abstract: Herein, Ti3C2Tx (MXene) was synthesized and mixed with polyvinyl alcohol (PVA) to fabricate PVA/MXene nanocomposites. The results confirmed that delaminated MXene was successfully synthesized. The nanocomposites were obtained via casting/evaporation method. The thermal stability was evaluated by thermogravimetric analysis (TGA). For the PVA composites with content of 2 wt% MXene (PVA‐MXene2), the thermal decomposition was retarded by approximately 20°C when the temperature was lower than 350°C compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…For instance, polyvinyl alcohol, polyvinylidene fluoride, polyurethane, and cellulose have been employed to incorporate with Ti 3 C 2 T x MXene to obtain better performance composites. [ 10–14 ] Cao et al. [ 10 ] prepared MXene/cellulose nanofiber composites by aqueous solution blending and the results indicated that the addition of MXene strengthened and toughened nanocomposites simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, polyvinyl alcohol, polyvinylidene fluoride, polyurethane, and cellulose have been employed to incorporate with Ti 3 C 2 T x MXene to obtain better performance composites. [ 10–14 ] Cao et al. [ 10 ] prepared MXene/cellulose nanofiber composites by aqueous solution blending and the results indicated that the addition of MXene strengthened and toughened nanocomposites simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…High flexibility, tensile strength, oxygen, and aroma barrier properties make them an excellent candidate for use in food packaging applications. [4][5][6] The drawback of PVA is nadir mechanical strength and high hydrophilicity attributable to abundant hydroxyl groups present in the carbon backbone, which makes it exceedingly easy to be plasticized by water, thus limiting its utilization. Graphene oxide with its exceptional properties, including high specific area, chemical resistance, thermal stability, super-mechanical strength has emanated as propitious nanomaterial to ameliorate both the water vapor barrier properties and mechanical properties.…”
mentioning
confidence: 99%
“…Despite the high loadings of filler promote poor mechanical properties, the composite material exhibited a strengthening effect as a result of adding MXene. This enhancement in mechanical properties, is related to the uniform dispersion of the filler and the hydrogen bonds that can form the -OH group between the MXene and the PVA matrix [ 30 ]. Thus, as demonstrated by the digital image in Figure 6 c, the MXene/PSZ-ABN/PVA film retains the flexibility of PVA.…”
Section: Resultsmentioning
confidence: 99%